Geographical and temporal distribution of multidrug-resistant Salmonella Infantis in Europe and the Americas - Guzinski, Jaromir; Potter, Joshua; Tang, Yue; Davies, Rob; Teale, Christopher; Petrovska, Liljana (Frontiers in Microbiology, 2024)
Recently emerged S. Infantis strains carrying resistance to several commonly used antimicrobials have been reported from different parts of the globe, causing human cases of salmonellosis and with occurrence reported predominantly in broiler chickens. Here, we performed phylogenetic and genetic clustering analyses to describe the population structure of 417 S. Infantis originating from multiple European countries and the Americas collected between 1985 and 2019. Of these, 171 were collected from 56 distinct premises located in England and Wales (E/W) between 2009 and 2019, including isolates linked to incursions of multidrug-resistant (MDR) strains from Europe associated with imported poultry meat. The analysis facilitated the comparison of isolates from different E/W sources with isolates originating from other countries. There was a high degree of congruency between the outputs of different types of population structure analyses revealing that the E/W and central European (Germany, Hungary, and Poland) isolates formed several disparate groups, which were distinct from the cluster relating to the United States (USA) and Ecuador/Peru, but that isolates from Brazil were closely related to the E/W and the central European isolates. Nearly half of the analysed strains/genomes (194/417) harboured the IncFIB(pN55391) replicon typical of the “parasitic” pESI-like megaplasmid found in diverse strains of S. Infantis. The isolates that contained the IncFIB(pN55391) replicon clustered together, despite originating from different parts of the globe. This outcome was corroborated by the time-measured phylogeny, which indicated that the initial acquisition of IncFIB(pN55391) likely occurred in Europe in the late 1980s, with a single introduction of IncFIB(pN55391)-carrying S. Infantis to the Americas several years later. Most of the antimicrobial resistance (AMR) genes were identified in isolates that harboured one or more different plasmids, but based on the short-read assemblies, only a minority of the resistance genes found in these isolates were identified as being associated with the detected plasmids, whereas the hybrid assemblies comprising the short and long reads demonstrated that the majority of the identified AMR genes were associated with IncFIB(pN55391) and other detected plasmid replicon types. This finding underlies the importance of applying appropriate methodologies to investigate associations of AMR genes with bacterial plasmids.